Effect of Anticoagulation Medication on the Thyroid Fine‐Needle Aspiration Pathologic Diagnostic Sufficiency Rate. (1st January 2016) - Denham, S. LeeAnn Wilson; Ismail, Aimen; Bolus, David N.; Lockhart, Mark E.
Abstract : Objectives: This study examined whether ultrasound‐guided thyroid fine‐needle aspiration (FNA) biopsy performed on patients taking anticoagulation medication results in a greater number of nondiagnostic pathologic samples due to a higher propensity to bleed, and thus fill the needle with blood rather than cellular material, compared to patients not taking anticoagulation medication. Methods: In this retrospective review, data were collected on 1100 patients who underwent ultrasound‐guided thyroid FNA over a 4‐year period. Of these patients, 438 were included. Each thyroid FNA was performed by a board‐certified radiologist using a 6‐pass capillary fill technique. Data including patient age, sex, nodule size, nodule consistency, and whether the patient was or was not taking anticoagulation medication (and, if they were, which medication) were recorded from the electronic medical record, and the nodule characteristics were confirmed on imaging by a senior radiology resident (postgraduate year 5). Results: Of the 438 patients included, 12 (2.7%) had an FNA aspirate that was deemed insufficient for diagnostic evaluation. Nondiagnostic pathologic yields were seen in 7 of the 309 patients (2.3%) who were not taking anticoagulation medication and 5 of 129 patients (3.9%) who were taking aspirin, warfarin, or clopidogrel, resulting in no statistically significant difference in the rates of nondiagnostic pathologic yields between the two groups ( P = .35). Conclusions: Based on these data, cessation of anticoagulation medication before thyroid FNA is not necessary to obtain sufficient cellular material for diagnosis, thus eliminating the need for procedural delays, patient inconvenience, and risks associated with anticoagulation medication cessation.